Penambahan Alat Produksi Mesin Perajang Guna Meningkatkan Produktivitas Usaha Mikro Gula Semut - Ananta Kusuma Yoga P.; Oktavima W; Ainurrofiq Ainurrofiq (IAI Darussalam, 2018)
This partnership program aims to provide solutions to the problems being faced by these two partners, namely: 1) Low productivity of ant sugar. Brown sugar must wait to be processed into ants sugar by manually shredded method with a capacity of 7 kg per 2 hours. 2) The resulting brown sugar products are only packaged in plastic bags, there is no brand or product identity color that can be used as a symbol, symbol or product logo, very simple and less attractive or less feasible to sell to consumers.3) On Micro Enterprises